(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud Computing and Virtualization are two booming technologies in this era. This paper is an attempt to correlate cloud with virtualization. This paper represents cloud as ‘automated virtualization’ and ‘how virtualization is a necessity to implement cloud’ is the main concern of paper. Cloud comes with business need in any IT organization to manage business cost and faster availability of required infrastructure. It comes by implementing defined processes and services to meet the increasing demand by business to reduce time of availability. Cloud computing is inclusive of virtualization and a way to implement it. While it is not uncommon to discuss them interchangeably; they are different approaches to solve the problem of maximizing the use of available resources. They differ in many ways and that also leads to some important considerations when selecting both or between the two. While understanding these technologies separately, we found that somewhere these technologies cannot be separated from each other. When we implement cloud, Virtualization is the technology which works as the right hand and is difficult to avoid. So, it will not wrong if we say that both of these technologies complement each other.